2021
DOI: 10.2147/dddt.s293025
|View full text |Cite
|
Sign up to set email alerts
|

L-Cysteine Provides Neuroprotection of Hypoxia-Ischemia Injury in Neonatal Mice via a PI3K/Akt-Dependent Mechanism

Abstract: Background: Previous work within our laboratory has revealed that hydrogen sulfide (H 2 S) can serve as neuroprotectant against brain damage caused by hypoxia-ischemia (HI) exposure in neonatal mice. After HI insult, activation of the phosphatidylinositol-3-kinase (PI3K)/ protein kinase B (Akt) signaling pathway has been shown to be implicated in neurorestoration processes. The goal of the current study was to determine whether the neuroprotective effects of H 2 S were mediated by the PI3K/Akt signaling pathwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 29 publications
(42 reference statements)
0
3
0
Order By: Relevance
“…H 2 S modulates the PI3K/Akt pathway in multiple cells. 34 , 35 , 36 , 37 For instance, H 2 S exerts cardioprotection against ischemia–reperfusion injury and against pressure‐overload heart failure models via Akt phosphorylation. 38 , 39 H 2 S has also been reported to modulate PI3K‐Akt signaling in vascular smooth muscle cells against high glucose‐induced apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…H 2 S modulates the PI3K/Akt pathway in multiple cells. 34 , 35 , 36 , 37 For instance, H 2 S exerts cardioprotection against ischemia–reperfusion injury and against pressure‐overload heart failure models via Akt phosphorylation. 38 , 39 H 2 S has also been reported to modulate PI3K‐Akt signaling in vascular smooth muscle cells against high glucose‐induced apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…This hypothesis of mechanism well fit with previous evidence showing that activation of PI3K/eNOS signaling by H 2 S directly modulated NO levels in BAEC [ 76 ] and exerts a protective effect in HG-induced injury in HUVEC cells [ 77 ]. Furthermore, the activation of this pathway has also been demonstrated to be beneficial in vivo, in a model of cardiac dysfunction associated with sepsis [ 78 ] as well as in neuronal hypoxia-ischemia injury or angiogenesis models [ 79 , 80 ].…”
Section: Discussionmentioning
confidence: 99%
“…Both Cho and MI levels increased after ischemia, indicating overactivation of glia after ischemia. Interestingly, AKT is a crucial regulator of cell energy metabolism, including cholinergic function, neurochemical differentiation, neuroprotection and inhibition of gliosis [ 30 ]. It was confirmed that activation of AKT regulated the levels of MI, Cho and NAA [ 18 ].…”
Section: Discussionmentioning
confidence: 99%